Determination of kinetic data through the fluidized bed combustion of chars made from vine and kiwi pruning wastes - D. M. Moreira; V. Ferreira; P. R. Resende; C. Pinho (Energy Reports, 2020)
This work concerns a preliminary study of the combustion of chars made from two different biomass species, vine and kiwi pruning wastes. The study was performed in a fluidized bed combustor, operating in a bubbling bed regime. The pellets were manufactured in a different installation, Viseu Polytechnic Institute, transported and, then carbonized in fixed bed batches at 900 C in a nitrogen atmosphere, in site, to obtain char. To acquire complete information on the combustion behavior, different sizes of char particles were subsequently burned in a bubbling fluidized bed and, through the measurement and subsequent analysis of the time progression of the CO2 in the flue gases, the evolution of the overall combustion resistance was obtained, and information on the combustion control was gathered. The evaluation of the relative importance of the kinetic and diffusive phenomena on the reaction was quantified, and it was observed that for the chars tested, the combustion was kinetically controlled. Applying the Arrhenius law to the kinetic data for each char, the corresponding pre-exponential factors and activation energies were obtained.
Keywords: 330; Biomass; Combustion; Fluidized bed; Pruning waste